BIBLICAL SPIRITUALITY, THE PSALMS, AND IDENTIFICATION WITH THE SUFFERING OF THE POOR: A CONTRIBUTION TO THE RECENT AFRICAN DISCUSSION ON PSALM 109 - Lombaard, Christo (Scriptura, 2012)
The discipline of Biblical Spirituality makes again explicit what has at times remained only implicit or has at times been overlooked in exegetical practice: that the biblical texts face two ways. On the one hand, the faith-in-historical-context which lead to the biblical texts being created, and on the other hand, the faith-inhistorical-context from which these texts have been/are being read, are both important to the discipline of Biblical Spirituality. The Psalms have played a particularly significant role throughout the respective histories of both lived biblical spiritualities and studies in the field of Biblical Spirituality. Specifically as it relates to the suffering of the poor, special attention is paid to Psalm 109: two recent African studies on this Psalm are taken into review, and drawing on all of the above, a new proposal is made for understanding verses 6-20.